Safety, pharmacokinetics, and antimalarial activity of the novel triaminopyrimidine ZY-19489: a first-in-human, randomised, placebo-controlled, double-blind, single ascending dose study, pilot food-effect study, and volunteer infection study. Issue 6 (June 2022) - Barber, Bridget E; Fernandez, Melissa; Patel, Hardik Babubhai; Barcelo, Catalina; Woolley, Stephen D; Patel, Harilal; Llewellyn, Stacey; Abd-Rahman, Azrin N; Sharma, Sunil; Jain, Mukul; Ghoghari, Ashok; Di Resta, Ilaria; et al.
Summary: Background: New antimalarials with novel mechanisms of action are needed to combat the emergence of drug resistance. Triaminopyrimidines comprise a novel antimalarial class identified in a high-throughput screen against asexual blood-stage Plasmodium falciparum . This first-in-human study aimed to characterise the safety, pharmacokinetics, and antimalarial activity of the triaminopyrimidine ZY-19489 in healthy volunteers. Methods: A three-part clinical trial was conducted in healthy adults (aged 18–55 years) in Brisbane, QLD, Australia. Part one was a double-blind, randomised, placebo-controlled, single ascending dose study in which participants enrolled into one of six dose groups (25, 75, 150, 450, 900, or 1500 mg) were randomly assigned (3:1) to ZY-19489 or placebo. Part two was an open-label, randomised, two-period cross-over, pilot food-effect study in which participants were randomly assigned (1:1) to a fasted-fed or a fed-fasted sequence. Part three was an open-label, randomised, volunteer infection study using the P falciparum induced blood-stage malaria model in which participants were enrolled into one of two cohorts, with participants in cohort one all receiving the same dose of ZY-19489 and participants in cohort two randomly assigned to receive one of two doses. The primary outcome for all three parts was the incidence, severity, and relationship to ZY-19489 of adverse events. Secondary outcomes were estimation of ZY-19489 pharmacokinetic parameters for all parts; how these parameters were affected by the fed state for part two only; and the parasite reduction ratio, parasite clearance half-life, recrudescent parasitaemia, and pharmacokinetic–pharmacodynamic modelling parameters for part three only. This trial is registered with the Australian New Zealand Clinical Trials Registry (ACTRN12619000127101, ACTRN12619001466134, and ACTRN12619001215112). Findings: 48 participants were enrolled in part one (eight per cohort for 25–1500 mg cohorts), eight in part two (four in each group, all dosed with 300 mg), and 15 in part three (five dosed with 200 mg, eight with 300 mg, and two with 900 mg). In part one, the incidence of drug-related adverse events was higher in the 1500 mg dose group (occurring in all six participants) than in lower-dose groups and the placebo group (occurring in one of six in the 25 mg group, two of six in the 75 mg group, three of six in the 150 mg group, two of six in the 450 mg group, four of six in the 900 mg group, and four of 12 in the placebo group), due to the occurrence of mild gastrointestinal symptoms. Maximum plasma concentrations occurred 5–9 h post-dosing, and the elimination half-life was 50–97 h across the dose range. In part two, three of seven participants had a treatment-related adverse event in the fed state and four of eight in the fasted state. Dosing in the fed state delayed absorption (maximum plasma concentration occurred a median of 12·0 h [range 7·5–16·0] after dosing in the fed state vs 6·0 h [4·5–9·1] in the fasted state) but had no effect on overall exposure (difference in area under the concentration–time curve from time 0 [dosing] extrapolated to infinity between fed and fasted states was −0·013 [90% CI −0·11 to 0·08]). In part three, drug-related adverse events occurred in four of five participants in the 200 mg group, seven of eight in the 300 mg group, and both participants in the 900 mg group. Rapid initial parasite clearance occurred in all participants following dosing (clearance half-life 6·6 h [95% CI 6·2–6·9] for 200 mg, 6·8 h [95% CI 6·5–7·1] for 300 mg, and 7·1 h [95% CI 6·6–7·6] for 900 mg). Recrudescence occurred in four of five participants in the 200 mg group, five of eight in the 300 mg group, and neither of the two participants in the 900 mg group. Simulations done using a pharmacokinetic–pharmacodynamic model predicted that a single dose of 1100 mg would clear baseline parasitaemia by a factor of 10 9 . Interpretation: The safety, pharmacokinetic profile, and antimalarial activity of ZY-19489 in humans support the further development of the compound as a novel antimalarial therapy. Funding: Cadila Healthcare and Medicines for Malaria Venture.